E-cadherin acts as a regulator of transcripts associated with a wide range of cellular processes in mouse embryonic stem cells. - Francesca Soncin; Lisa Mohamet; Sarah Ritson; Kate Hawkins; Nicoletta Bobola; Leo Zeef; Catherine L R Merry; Christopher M Ward (PLoS ONE)
Background We have recently shown that expression of the cell adhesion molecule E-cadherin is required for LIF-dependent pluripotency of mouse embryonic stem (ES) cells. Methodology In this study, we have assessed global transcript expression in E-cadherin null (Ecad-/-) ES cells cultured in either the presence or absence of LIF and compared these to the parental cell line wtD3. Results We show that LIF has little effect on the transcript profile of Ecad-/- ES cells, with statistically significant transcript alterations observed only for Sp8 and Stat3. Comparison of Ecad-/- and wtD3 ES cells cultured in LIF demonstrated significant alterations in the transcript profile, with effects not only confined to cell adhesion and motility but also affecting, for example, primary metabolic processes, catabolism and genes associated with apoptosis. Ecad-/- ES cells share similar, although not identical, gene expression profiles to epiblast-derived pluripotent stem cells, suggesting that E-cadherin expression may inhibit inner cell mass to epiblast transition. We further show that Ecad-/- ES cells maintain a functional β-catenin pool that is able to induce β-catenin/TCF-mediated transactivation but, contrary to previous findings, do not display endogenous β-catenin/TCF-mediated transactivation. We conclude that loss of E-cadherin in mouse ES cells leads to significant transcript alterations independently of β-catenin/TCF transactivation.